2012 IEEE International Ultrasonics Symposium 2012
DOI: 10.1109/ultsym.2012.0562
|View full text |Cite
|
Sign up to set email alerts
|

Efficient implementation of a real-time dynamic synthetic aperture beamformer

Abstract: Synthetic aperture (SA) imaging techniques can provide high resolution over imaging depths, unlike a conventional receive focusing methods (CRDF) that suffered from a considerable degradation in resolution far from a transmit focal depth.However, it is difficult to incorporate SA on modern medical ultrasound imaging systems due to its high computational complexity. In this paper, the efficient implementation of a real-time dynamic SA beamformer where the number of synthetic scanlines is dynamically adjusted ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A recursive and iterative method can be used to compute the square roots efficiently [49]. In [50] only every 32nd delay is truly computed and the remaining delays are interpolated. Some works and industrial products have focused on a low power, portable imager implementation [1]- [6], [51].…”
Section: Previous Workmentioning
confidence: 99%
“…A recursive and iterative method can be used to compute the square roots efficiently [49]. In [50] only every 32nd delay is truly computed and the remaining delays are interpolated. Some works and industrial products have focused on a low power, portable imager implementation [1]- [6], [51].…”
Section: Previous Workmentioning
confidence: 99%
“…Other works [15], [16], [17], [18] have shown that a feasible alternative is to try to compute all delay coefficients onthe-fly on-chip. Since this computation involves the evaluation of complex functions like square roots, it is mandatory to identify accurate, fast and low-area approximation circuits [19], [20]. In particular, we have shown [5], [6] how a highly efficient architecture can be devised by accepting some inaccuracy in the calculation of the delays.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the quad Virtex-5 LX330 FPGA solution [33] our integrated approach provides only 2.75× less processing throughput at a much smaller form factor and power budget. The 8-core TI Keystone DSP-based solution [36] targets low-power, low-cost ultrasound devices.…”
Section: B Estimated Powermentioning
confidence: 99%
“…Since Ekho can be scaled down to support such setups, a comparison with these 2-D systems is appropriate. In [33], a 128 channel synthetic aperture 2-D BF built from four Virtex-5 LX330 FPGAs is presented. Sixteen SLs are computed in parallel at a sampling rate of 40 MHz.…”
Section: Introductionmentioning
confidence: 99%